Idealized simulations reveal the potential for widespread high supersaturation in marine tropical deep convection - Chunying Fan; Siwei Li; Lin Zang; Zengxin Pan; Feiyue Mao; Fan Liu; Wei Gong; Daniel Rosenfeld (Atmospheric Research, 2026)

Metabolic complementarity and enhanced biofilm formation drive the synergistic symbiosis of lactic acid bacteria and yeast in Tibetan kefir - Liangli Wu; Jianwei Zang; Luyao Xiao; Chang Xu; Xia Fan; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Tao Lin; Wei Li (International Dairy Journal, 2026)

Fermentation of ginseng juice by Lactiplantibacillus plantarum SP055 and Limosilactobacillus fermentum LB-9: Fermentation characteristics and ginsenoside biotransformation pathways - Jianwei Zang; Wei Liu; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Yimeng Kou; Chunling Meng; Jiamin Xu; Tao Lin; Xin Rui; Dan Gan; et al. (Food Microbiology, 2026)

From fermentation to function: a critical review of lactic acid bacteria redesign for functional foods and precision nutrition - Jianwei Zang; Luyao Xiao; Xiaogan Zhao; Yibo Shi; Kai Ma; Changliang Zhang; Shuo Geng; Xin Rui; Tao Lin; Wei Li (Critical Reviews in Food Science and Nutrition, 2026)

Overexpression of DR1372 gene from Deinococcus radiodurans improves the salt and drought tolerance in soybean - Lili Zhou; Ke Zang; Xinyan Liu; Peilin Wang; Wenfang Guo; Xiaofeng Su; Mahideen Afridi; Jin Wang; Min Lin; Hongmei Cheng; Huiming Guo (Plant and Soil, 2026)

CRISPR/Cas9-mediated knockout of CsRDL1 decreases the susceptibility of Chilo suppressalis to cyproflanilide - Jungang Zhou; Ziren Zang; Hongshuai Gao; Jinjun Sun; Lina Xu; Qiao Gao; Hualiang He; Wenbing Ding; Lin Qiu; Youzhi Li (Pesticide Biochemistry and Physiology, 2026)

Lactobacillus helveticus MB2-1 powders prepared using different drying strategies reshape dominant intermolecular interaction patterns and structural network formation during fermentation of coconut-based yogurt alternatives - Jianwei Zang; Yimeng Kou; Yibo Shi; Xiaotong Hao; Shiyuan Feng; Chunling Meng; Jiamin Xu; Di Yu; Tao Lin; Kai Ma; Changliang Zhang; Mingsheng Dong; et al. (Food and Bioproducts Processing, 2026)

Chloride ions-assisted high-efficiency natural seawater splitting enabled by noble-metal-free MnOx(OH)y/GaN nanowires - Yumeng Li; Liang Qiu; Xiantong Zheng; Lin Yao; Muhammad Salman Nasir; Zijian Huang; Ying Li; Yixin Li; Ding Wang; Wenxing Yang; Jianyang Zang; Ping Wang; et al. (Science Bulletin, 2026)

Salidroside Alleviates Mobocertinib-Induced Cardiotoxicity by Improving Cardiac Electrophysiology - Chi Yan; Xiaohong Liu; Xiaoyan Zhang; Pei Wei; Xuefang Li; Dongxu Li; Guhao Zhang; Meng Li; Xiayan Zang; Guangjian Lu; Fei Lin (Cardiovascular Toxicology, 2026)

Tropical-origin lactic acid bacteria co-fermentation enables protein network restructuring and glucose-lipid metabolic regulation in coconut-based yogurt alternatives - Jianwei Zang; Yimeng Kou; Xia Fan; Xin Rui; Tao Lin; Wei Li (Innovative Food Science & Emerging Technologies, 2026)

A tropical fermented-food-derived Lactiplantibacillus plantarum SP055 alleviates DSS-induced colitis through coordinated regulation of gut microbiota and intestinal barrier function - Jianwei Zang; Yibo Shi; Xiaotong Hao; Xia Fan; Yimeng Kou; Wanxiang Zhang; Luyao Xiao; Chang Xu; Tao Lin; Xin Rui; Dan Gan; Wei Li (Food Bioscience, 2026)

Copolymer hydrogel formed by κ-carrageenan and chickpea protein amyloid fibrils: From rheological properties to regulation of aggregation morphology - Lin-Da Zhang; Xiao-Lei Zang; Yu-Nan Pan; Jia-Cheng Liu; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Hydrocolloids, 2026)

Regulating surface hydroxyl anchoring sites to tailor metal–support interactions in Ni–FAU bifunctional materials for integrated CO₂ capture and methanation - Pengchao Zang; Jiyun Tang; Xiaozhe Wang; Wei Dong; Hao Zhang; Lin Cui; Shouyan Chen; Guojie Qi; Yong Dong (Chemical Engineering Journal, 2026)

Spatially explicit nutritional landscapes couple with environmental variables to shape nekton distribution patterns - Na Zang; Wenjun Zheng; Bilin Liu; Shaoqin Wang; Xinjun Chen; Dongming Lin (Limnology and Oceanography, 2026)
Species distributions are traditionally explained by environmental gradients, yet the role of nutritional factors, particularly essential fatty acids (EFA), remains poorly understood. We test the hypothesis that zooplankton EFA form a nutritional landscape that couples with environmental variables to shape the biogeography of nekton. We integrated spatial data of zooplankton EFA (arachidonic acid (ARA, 20:4n‐6), eicosapentaenoic acid (EPA, 20:5n‐3), and docosahexaenoic acid (DHA, 22:6n‐3)) with environmental variables into joint species distribution models (JSDMs). We compared explanatory power across three model types: JSDM_Env (environmental variables only), JSDM_EFA (EFA variables only), and JSDM_EnvEFA (combined environmental and EFA variables). Spatial analysis revealed significant heterogeneity in EFA concentrations, with elevated levels of EPA and DHA concentrated in the northeastern region. Model results showed that both EFA and environmental variables were effective predictors of species distributions. The JSDM_EnvEFA model exhibited the greatest explanatory power (mean AUC = 0.96, mean R 2 = 0.40), with variance decomposition revealing that EFA explained more variance than environmental variables (EFA: 54%, environment: 32%). Notably, EPA contributed up to 37% of the total explained variance, surpassing the influence of sea surface temperature (14%). Incorporating EFA also changed the estimated strength of species associations, suggesting that co‐occurrence patterns may be shaped by shared nutritional dependencies. Our results demonstrate that EFA availability is as critical as environmental variables in determining nekton species distributions, which support the spatial coupling hypothesis, demonstrating that EFA landscapes couple with environmental variables to structure pelagic communities. These findings establish nutritional landscape as a critical dimension of marine biogeography, providing a novel framework for predicting community responses to global change.

Aircraft-observed High Supersaturation Indicates the Potential of Aerosol Convective Invigoration Effect - Zengxin Pan; Daniel Rosenfeld; Lin Zang; Feiyue Mao; Jiwen Fan (Advances in Atmospheric Sciences, 2026)

Integrating stimulation and CO2 storage in natural gas hydrate reservoirs: visualization of CO2-foam fracturing and hydrate self-sealing - Kunlin Ma; Jingsheng Lu; Zhibin Sha; Dongliang Li; Decai Lin; Xiaoya Zang; Deqing Liang (Journal of Cleaner Production, 2026)

Sulfonylurea receptor integrates calcium homeostasis and insulin-like peptide signaling to regulate energy metabolism and larval development in Hyphantria cunea - Yue-Cheng Zhao; Rong-Man Gou; Haneef Tariq; Xi-Lin Li; Lian-Sheng Zang; Li-Wen Song (Insect Biochemistry and Molecular Biology, 2026)

Quality formation in corn kernels during postharvest ripening: the influence of storage conditions on phenolic components and antioxidant activity - Fuyin Zhao; Haohai Li; Rixin Zang; Jiahui Pan; Jinying Zhu; Lin Xiu; Huimin Liu; Mingzhu Zheng; Meihong Liu; Jingsheng Liu (Food Chemistry, 2026)

The Evidence for Nekton Distribution Modulated by Plankton Abundance in the High Seas Area of Northwest Pacific During Summer Season - Na Zang; Dongming Lin; Yizhen Shan; Bilin Liu; Xinjun Chen (Fisheries Oceanography, 2026)
Deterministic biotic interactions and abiotic conditions define species distributions and abundance, with plankton underpinning food webs to spatially structure predator distributions through bottom‐up processes. However, characterizing the mechanism underlying species abundance formation in an oceanic system remains challenging. We applied piecewise structural equation models to examine plankton abundance and environmental conditions in nekton assembly, combined with joint species distribution models to investigate the distribution associations between nekton and plankton in the high‐seas area of northwest Pacific. Results revealed that nekton distribution (fish and squid) showed significant associations with plankton abundance, where zooplankton correlations markedly surpassed phytoplankton associations. The fluctuations of plankton abundance directly influence nekton abundance, whereas the effects of environmental conditions were mediated indirectly through effects on plankton. These findings affirm the primacy of plankton abundance in driving nekton distribution and advance understanding of how bottom‐up trophic pathways modulate nekton distribution dynamics in pelagic ecosystems.

Assimilating FY-4B satellite aerosol data to improve PM₂.₅ and surface shortwave radiation prediction - Fangzheng Hu; Feiyue Mao; Yi Zhang; Jia Hong; Lin Zang; Zhaoliang Zeng; Sicong Lin; Wei Gong; Daniel Rosenfeld (Atmospheric Research, 2026)

Atmospheric CO₂ concentration gradients at the coastal region of the Yangtze River Delta: Patterns and drivers - Yi Lin; Honggang Lv; Kehan Chen; Peng Guo; Yifei Jiang; Lin Xiao; Tienan Zhao; Haiyan Wang; Yuanyuan Chen; Kunpeng Zang; Shuangxi Fang (Atmospheric Research, 2026)

Collagen type XV regulation via MMP2-dependent degradation governs ovarian development in the rice stem borer, Chilo suppressalis - Yue Li; Suijie Kuang; Yan Tang; Zhuotian Yao; Yechen Pan; Ziren Zang; Yang Cui; Hongshuai Gao; Lin Qiu; Yansong Xiao; Tin Liu; Qi Su; et al. (Insect Biochemistry and Molecular Biology, 2026)

Comprehensive diurnal and nocturnal surface NO2 concentration retrieval with seamless temporal and spatial coverage - Yi Zhang; Lin Zang; Yuqing Su; Jingru Yang; Ying Yang; Feiyue Mao (Atmospheric Environment, 2026)

The Time Reliable Effect of Probiotic Clostridium butyricum on the Growth of Spotted Sea Bass (Lateolabrax maculatus) - Yiqin Deng; Liwen Xu; Keng Yang; Ziyang Lin; Shujun Zang; Kui Jiang; Wangdong Li; Nabil A. Ibrahim; Hongling Ma; Changhong Cheng; Juan Feng (Probiotics and Antimicrobial Proteins, 2026)

Aerosol-cloud layer detection algorithm of the DQ-1/ACDL - Feiyue Mao; Weiwei Xu; Zengxin Pan; Lin Zang; Ge Han; Linxin Dai; Xiuqing Hu; Weibiao Chen; Wei Gong (Remote Sensing of Environment, 2026)

Controllable synthesis of organic phosphonic acids functionalized Ti3C2Tx for enhanced and selective uranium extraction - Siyi Wang; Pengcheng Zhang; Ziyang Wang; Xiangjian Meng; Yu Zang; Fei Wu; Lin Wang; Weiqun Shi; Suwen Chen (Chemical Engineering Journal, 2026)

Fabrication and characterization of starch-based edible films loaded with Lactiplantibacillus plantarum STB9b for pork preservation - Jianwei Zang; Yue Hu; Tao Lin; Xia Fan; Yimeng Kou; Yibo Shi; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Wei Li (Food Packaging and Shelf Life, 2025)

Optimizing MERRA-2 aerosol extinction coefficient by fusing CALIPSO and SAGE observations with machine learning - Jingru Yang; Lin Zang; Feiyue Mao; Yi Zhang; Weiwei Xu; Fan Liu; Tingting Liu (Atmospheric Environment, 2025)

Valve gaping behavior of bivalves under compound marine heatwaves and acidification extremes - Yang Xu; Xin Luo; Yu He; Xiaoning Zang; Weiguo Lin; Yong Liu; Liqiang Zhao (Marine Environmental Research, 2025)

Dual-ion charge storage mechanism in polypyrrole cathodes for zinc-ion hybrid capacitors - Jiali Zhang; Tao Xue; Yongbiao Mu; Hongjie Li; Chao Yang; Limin Zang; Lin Zeng (Chemical Engineering Journal, 2025)

Satellite-Based Emission Inversion for Air Pollutants and Greenhouse Gases: A Review - Zhe Jiang; Jintai Lin; Tai-Long He; Fei Jiang; Jianbing Jin; Kai Qin; Lu Shen; Panpan Yang; Zengliang Zang; Lin Zhang; Yuzhong Zhang; Bo Zheng; et al. (Journal of Meteorological Research, 2025)

Tree species classification via a two-stage deep learning framework: integration of enhanced spectral reconstruction with classifiers - Zhiping Lin; Yuhao Yuan; Qun Zang; Zhongmou Fan (International Journal of Remote Sensing, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Application of artificial intelligence in the rapid determination of moisture content in medicine food homology substances - Mengyu Zhang; Boran Lin; Shudi Zhang; Cheng Peng; Chang Li; Tingting Feng; Lian Li; Aoli Wu; Chunguo Yang; Wentian Wang; Shouyao Huang; Lei Nie; et al. (Food Chemistry, 2025)

Quasi-Solid-State Electrolytes: Bridging the gap between solid and liquid electrolytes for zinc-ion batteries - Tao Xue; Jinpeng Guan; Yongbiao Mu; Meisheng Han; Chao Yang; Limin Zang; Lin Zeng (Chemical Engineering Journal, 2025)

In situ multifunctional gel for hormone-immune therapy of ovarian cancer and prevention of postoperative adhesion - Yankun Zhang; Yanbin Shi; Hengchang Zang; Xiaogang Zhao; Xianglei Fu; Shengnan Qiu; Yuan Zhang; Yingying Liu; Xiaoyu Wan; Zengmei Li; Yaqi Li; Jiamin Zhou; et al. (Chemical Engineering Journal, 2025)

Online monitoring of water quality in industrial wastewater treatment process based on near-infrared spectroscopy - Cheng Peng; Zeming Wu; Shudi Zhang; Boran Lin; Lei Nie; Weilu Tian; Hengchang Zang (Water Research, 2025)

Rapid Indian Monsoon response to the Younger Dryas event in the Southeastern Tibetan Plateau - Xiqian Wang; Liangcheng Tan; Ashish Sinha; Hai Xu; Haiwei Zhang; Jianghu Lan; Jin Zhang; Tianli Wang; Dong Li; Le Ma; Jingjie Zang; Xing Cheng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Nanomorphic copper phosphate as a lightless catalyst for singlet oxygen generation: Mechanistic insights and comparative analysis - Weihao Cong; Lin Zang; Mengting Pan; Liyuan Zhang; Yan Zhao; Weiheng Kong (Journal of Environmental Chemical Engineering, 2025)

Modulation of CO2 hydrogenation selectivity through microstructural phase evolution-induced electronic transfer on Ni/TiO2 - Yunhao Zang; Xuetan Lin; Jiangying Qu; Feng Gao; Jianfeng Gu; Taipeng Wei; Rongrong Wang (Fuel, 2025)

Long-term organic farming improves the red soil quality and microbial diversity in subtropics - Yongkang Wen; Wei Yao; Taobing Yu; Lang Cheng; Qing Zhang; Jida Yang; Fangding Lin; Hongye Zhu; Anna Gunina; Yadong Yang; Kevin Z. Mganga; Zhaohai Zeng; et al. (Agriculture, Ecosystems & Environment, 2025)

On water entry/exit of free-fall lifeboats into regular waves: A computational fluid dynamics study - Ningge Fan; Gong Chen; Binyi Liang; Yingying Lin; Zhen Yue; Di Wang; Mengyan Zang; Shunhua Chen (Ocean Engineering, 2025)

Gem-like starch granules engineered with different crystalline starches - Ruikang Lin; Xufeng Zang; Wenjie Zhang; Ying Tian; Yishan Fang (Food Chemistry, 2025)

Large warming of tropical convective anvils masked by their underlying clouds - Zengxin Pan; Daniel Rosenfeld; Lin Zang; Jianhua Yin; Feiyue Mao (Remote Sensing of Environment, 2025)

K2CO3-doped CaO-based sorbent for CO2 capture: Performance studies and promotion mechanisms - Pengchao Zang; Jiyun Tang; Yihui Tao; Hao Zhang; Xiaozhe Wang; Lin Cui; Shouyan Chen; Pei Zhao; Yong Dong (Chemical Engineering Journal, 2025)

DNAzyme assisted single amplification for FEN1 activity detection using a personal glucose meter - Mingxi Li; Weijie Zang; Shuiliang Wang; Zhannuo Lin; Shu Liu; Yiling Chen; Xiaohui Ruan; Yuanfang Luo; Chao Xing; Chunhua Lu (Analytica Chimica Acta, 2025)

Design and experimental analysis of real-time detection system for The seeding accuracy of rice pneumatic seed metering device based on the improved YOLOv5n - He Xing; Yikai Wan; Peng Zhong; Junjiang Lin; Mingtao Huang; Ru Yang; Ying Zang (Computers and Electronics in Agriculture, 2024)

Diurnal hourly near-surface ozone concentration derived from geostationary satellite in China - Yi Zhang; Lin Zang; Jie Song; Jingru Yang; Ying Yang; Feiyue Mao (Science of The Total Environment, 2024)

Can digital technology adoption promote environmental innovation in small and medium-sized enterprises (SMEs)? Evidence from China - Huanyong Ji; Lei Lin; Jun Wan; Jiyuan Zang (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

DEM-CFD coupling simulation and optimisation of rice seed particles seeding a hill in double cavity pneumatic seed metering device - He Xing; Xiaoman Cao; Peng Zhong; Yikai Wan; Junjiang Lin; Yu Zang; Guozhong Zhang (Computers and Electronics in Agriculture, 2024)

Corrigendum to “Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots” [Chem. Eng. J. 486 (2024) 150196] - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Correlation between Antibiotics-Resistance, Virulence Genes and Genotypes among Klebsiella pneumoniae Clinical Strains Isolated in Guangzhou, China - Yi-Lin Hu; Shui-Lian Bi; Zang-Yun Zhang; Nian-Qing Kong (Current Microbiology, 2024)

Dual amplification dynamic DNA network system for CRISPR/Cas12a based p53 gene detection - Tengkai Wang; Kexin Ding; Xinli Wang; Zehua Wang; Gengjun Liu; Yufei Zang; Shengxiang Lin; Hong Zhou; Qian Wang (Analytica Chimica Acta, 2024)

CD146, a therapeutic target involved in cell plasticity - Zhenzhen Wu; Yuzhe Zang; Chuyi Li; Zhiheng He; Jingyu Liu; Zhaoqi Du; Xinran Ma; Lin Jing; Hongxia Duan; Jing Feng; Xiyun Yan (Science China Life Sciences, 2024)

Phthalate and DINCH exposure and ovarian reserve markers among women seeking infertility care - Yangqian Jiang; Yiqun Xu; Shuxin Xiao; Xianxian Zhu; Hong Lv; Lu Zang; Shuifang Lei; Xin Xu; Bo Xu; Xiumei Han; Jin Zhu; Jiangbo Du; et al. (Science of The Total Environment, 2024)

Flavor profile and quality of strawberry wine are improved through sequential fermentation with indigenous non-Saccharomyces yeasts and Saccharomyces cerevisiae - Bo Yang; Shijiao Liu; Hongwen Zang; Yiwei Dai; Sufang Zhang; Xinping Lin; Huipeng Liang; Yingxi Chen (Food Bioscience, 2024)

Bilayer micropatterned hydrogel scaffolds loaded with ADSCs improved integration with regenerated tissue and diabetic wound healing - Hongyun Zang; Huamin Jiang; Jiana Huang; Mariya Mohamad El Akkawi; Ling Yan; Kaiying Liang; Zhaoyi Lin; Zirui Zhu; Yan Li (Chemical Engineering Journal, 2024)

Sugarcane ScOPR1 gene enhances plant disease resistance through the modulation of hormonal signaling pathways - Wenhui Zou; Tingting Sun; Yao Chen; Dongjiao Wang; Chuihuai You; Shoujian Zang; Peixia Lin; Qibin Wu; Yachun Su; Youxiong Que (Plant Cell Reports, 2024)

Study on Sensitivity Mechanism of Low-Permeability Sandstone Reservoir in Huilu Area of Pearl River Mouth Basin - Hongbo Li; Lin Ding; Qibiao Zang; Qiongling Wu; Yongkun Ma; Yuchen Wang; Sandong Zhou; Qiaoyun Cheng; Xin Tian; Jiancheng Niu; Mengdi Sun (Journal of Marine Science and Engineering, 2024)
Reservoir sensitivity is a parameter that is used to evaluate the degree of change in reservoir permeability under the influence of external fluids. Accurate evaluation of reservoir sensitivity is conducive to the optimization of fluid parameters during exploration and development. Taking the Wenchang Formation and Enping Formation of the Paleogene in the Huilu area of the Pearl River Mouth Basin as the research object, reservoir sensitivity experiments were carried out. Combined with the corresponding experimental results obtained using methods such as thin section identification, scanning electron microscopy (SEM), X-ray diffraction (XRD), mercury intrusion porosimetry (MIP), and screening analysis, based on mineral sensitization and pore structure sensitization, qualitative and quantitative evaluations of reservoir sensitivity were carried out, and factors affecting sensitivity and sensitization mechanisms were analyzed. This work shows the following: (1) The sandstone reservoirs in the two areas have the same clay type, but the total clay content of the Wenchang Formation is greater than that of the Enping Formation. The porosity of the Wenchang Formation is less developed than the Enping Formation. (2) The Wenchang Formation has weak or moderately weak water sensitivity and moderately weak or moderately strong flow velocity sensitivity. The water sensitivity of the Enping Group samples is moderately weak or moderately strong, the flow rate sensitivity is moderately weak, the alkali sensitivity is weak, the acid sensitivity is moderately weak, and the salinity sensitivity is moderately weak or moderately strong. (3) The sensitivity of the Wenchang Formation is mainly affected by the content of clay minerals. The sensitivity of the Enping Formation is also affected by the clay content and type. Although the clay content is not high, the permeability is more susceptible to sensitivity due to the pore structure and debris particle distribution characteristics. These conclusions are beneficial for the selection of fluid parameters and efficient reservoir development.

Atmospheric CO2 in the megacity Hangzhou, China: Urban-suburban differences, sources and impact factors - Yuanyuan Chen; Yanran Lu; Bing Qi; Qianli Ma; Kunpeng Zang; Yi Lin; Shuo Liu; Fengmei Pan; Shan Li; Peng Guo; Lihan Chen; Wengang Lan; et al. (Science of The Total Environment, 2024)

Fast and efficient As(III) removal from water by bifunctional nZVI@NBC - Jiuwan Wang; Mengfan Chen; Yulian Han; Congting Sun; Ying Zhang; Shuyan Zang; Lin Qi (Environmental Geochemistry and Health, 2024)

Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Two-dimensional interfacial enhanced CO2 adsorption performance of porous organic amine solids: Structure-activity relationships and DFT calculations - Pengchao Zang; Jiyun Tang; Hao Zhang; Xiaozhe Wang; Lin Cui; Juan Chen; Pei Zhao; Yong Dong (Chemical Engineering Journal, 2024)

Salinity as a key factor affecting viral activity and life strategies in alpine lakes - Lin Zang; Yongqin Liu; Nianzhi Jiao; Kevin Xu Zhong; Xuanying Song; Yunlan Yang; Lanlan Cai; Keshao Liu; Guannan Mao; Mukan Ji; Rui Zhang (Limnology and Oceanography, 2024)
Viruses are major players in the biosphere, yet little is known about their dynamics and life strategies in alpine lakes, particularly those on the Tibetan Plateau. We investigated microbial abundance, viral dynamics, and viral life strategies in 10 high‐altitude Tibetan lakes and found that they harbor high levels of active viruses. Salinity was identified as a crucial factor influencing viral abundance, dynamics, as well as viral life strategies. Lytic and lysogenic viral productions in moderate‐ and high‐salinity lakes were significantly higher than those in freshwater lakes. A trade‐off between viral life strategies resulted in a switch from lysis to lysogeny in high‐salinity lakes. Virus‐mediated cell lysis and virus decay in sampled Tibetan lakes could release about 162.72 and 2.84 μ g C L −1 d −1 , respectively. These findings revealed the crucial role of viruses in the carbon cycle of Tibetan lakes, and a switch in viral life strategies may impact their contribution to the carbon cycle. The potential impact of salinity changes triggered by climate change on the carbon cycle in alpine lakes worldwide is highlighted.

Prediction of MSW pyrolysis products based on a deep artificial neural network - Yunfei Zang; Shaoheng Ge; Yu Lin; Lijie Yin; Dezhen Chen (Waste Management, 2024)

Self-growing micro/nano hexagonal cyclodextrins based on dual enzyme synergism and low-temperature induction - Ruikang Lin; Xufeng Zang; Chao Yuan; Bing Yu; Pengfei Liu; Yishan Fang; Bo Cui (Chemical Engineering Journal, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Mechanism of sulfur-guided CO2 selective hydrogenation through modulation of surface intermediate over Ni/ZrO2 catalysts - Yunhao Zang; Ziyi Zhang; Yan Wang; Jiangying Qu; Feng Gao; Jianfeng Gu; Xuetan Lin; Taipeng Wei (Chemical Engineering Journal, 2024)

The effect of miR-223-3p on endothelial cells in coronary artery disease - Boxin Zhao; Yunhui Zang; Lin Gui; Yingyu Xiang; Zhiyong Zhang; Xueyuan Sun; Jingyao Fan; Lijuan Huang (In Vitro Cellular & Developmental Biology - Animal, 2024)

Hydroxyl-groups engineering of triazole-based polymers for efficient photocatalytic hydrogen peroxide production - Feng Lin; Zhaoyang Ju; Yao Li; Jia Liu; Liyong Ding; Haijie Ben; Yulin Wang; Yuechao Wu; Ying Lei; Huiming Zeng; Shaohong Zang; Jun Chen; et al. (Journal of Cleaner Production, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Diversity and function of mountain and polar supraglacial DNA viruses - Yongqin Liu; Nianzhi Jiao; Kevin Xu Zhong; Lin Zang; Rui Zhang; Xiang Xiao; Yi Shi; Zhihao Zhang; Ye Tao; Liping Bai; Bianli Gao; Yunlan Yang; et al. (Science Bulletin, 2023)

Strategies to improve CaO absorption cycle stability and progress of catalysts in Ca-based DFMs for integrated CO2 capture-conversion: A critical review - Pengchao Zang; Jiyun Tang; Xiaoyang Zhang; Lin Cui; Juan Chen; Pei Zhao; Yong Dong (Journal of Environmental Chemical Engineering, 2023)

Delays in heading and improvements in both spikelet number and spike length are associated with the Aegilops tausschii photoperiod-sensitive ppd-D1b allele - Shunzong Ning; Laibin Zhao; Shijie Li; Shengke Li; Tianqing Zang; Yu’e Liu; Hongkun Yang; Xuejiao Chen; Xue Chen; Yingjin Yi; Ming Hao; Lianquan Zhang; et al. (Cereal Research Communications, 2023)

Development of Au8 nanocluster-based fluorescent strip immunosensor for sensitive detection of aflatoxin B1 - Zi-Hui Shao; Aoqiang Zhai; Yue Hua; Hui-Lin Mo; Fuwei Xie; Xueli Zhao; Ge Zhao; Shuang-Quan Zang (Analytica Chimica Acta, 2023)

Temporal patterns and determinants of atmospheric methane in Suzhou, the Yangtze River Delta - Na Guo; Huijuan Lin; Yi Lin; Fenfen Wei; Kunpeng Zang; Shuangxi Fang (Atmospheric Pollution Research, 2023)

Sulfur and water management mediated iron plaque and rhizosphere microorganisms reduced cadmium accumulation in rice - Yili Zang; Jie Zhao; Weikang Chen; Lingli Lu; Jiuzhou Chen; Zhi Lin; Yabei Qiao; Haizhong Lin; Shengke Tian (Journal of Soils and Sediments, 2023)

Three-dimensional bending and free vibration analyses of laminated cylindrical panel with/without elastic foundation using two-dimensional discrete method - Wenbin Ye; Quansheng Zang; Jun Liu; Fan Yang; Gao Lin (Soil Dynamics and Earthquake Engineering, 2023)

Natural iron minerals in an electrocatalytic oxidation system and in situ pollutant removal in groundwater: Applications, mechanisms, and challenges - Ganning Zeng; Ji Wang; Mengzheng Dai; Yutong Meng; Hongwei Luo; Qian Zhou; Liangyu Lin; Kunpeng Zang; Zhu Meng; Xiangliang Pan (Science of The Total Environment, 2023)

Hydroxyl radicals in natural waters: Light/dark mechanisms, changes and scavenging effects - Ganning Zeng; Ming Shi; Mengzheng Dai; Qian Zhou; Hongwei Luo; Liangyu Lin; Kunpeng Zang; Zhu Meng; Xiangliang Pan (Science of The Total Environment, 2023)

Evaluation of imide substance from Streptomyces atratus PY-1 for the biocontrol of Phytophthora blight - Chaoqun Zang; Tingting Kong; Bingbing Liang; Xiaozhou Liu; Jinhui Xie; Ying Lin; Xue Pei; Shuyi Yu; Chunhao Liang (European Journal of Plant Pathology, 2023)

Corrigendum to “Discovery and characterization of the flavonoids in Cortex Mori Radicis as naturally occurring inhibitors against intestinal nitroreductases” [Chem. Biol. Interact. 368 (2022) 110222] - Xi Chen; Yue Han; Lu Chen; Qian-Lin Tian; Yu-Ling Yin; Qi Zhou; Shi-Zhu Zang; Jie Hou (Chemico-Biological Interactions, 2023)

Evaluation of a GNSS for wave measurement and directional wave spectrum analysis - Hanbin Gu; Xiaoan Zhu; Rui Shan; Jun Zang; Ling Qian; Pengzhi Lin (Ocean Engineering, 2023)

Association of phthalate exposure with low birth weight in couples conceiving naturally or via assisted reproductive technology in a prospective birth cohort - Lu Zang; Hong Lv; Jiangbo Du; Yitao Pan; Yuan Lin; Jiayin Dai (Science of The Total Environment, 2023)

Meniscus inspired flexible superhydrophobic coating with remarkable erosion resistance for pipeline gas transmission - Xuerui Zang; Xuewen Cao; Weiwei Zheng; Tianxue Zhu; Yonggang Lei; Jianying Huang; Zhong Chen; Lin Teng; Jiang Bian; Yuekun Lai (Chemical Engineering Journal, 2023)

Spatio-temporal association mining of intercity PM2.5 pollution: Hubei Province in China as an example - Jiangping Chen; Xiaofeng Song; Lin Zang; Feiyue Mao; Jianhua Yin; Yi Zhang (Environmental Science and Pollution Research, 2023)

Glibenclamide Directly Prevents Neuroinflammation by Targeting SUR1-TRPM4-Mediated NLRP3 Inflammasome Activation In Microglia - Yihua He; Yuan Chang; Yuqin Peng; Juan Zhu; Kewei Liu; Jiancong Chen; Yongming Wu; Zhong Ji; Zhenzhou Lin; Shengnan Wang; Sohan Gupta; Nailiang Zang; et al. (Molecular Neurobiology, 2022)

Elevation of microRNA-365 impedes malignant behaviors of gastric cancer cells by inhibiting PAX6 - Dan Hong; Aimin Zang; Zhiyu Wang; Lin Yang; Guanying Ren; Chong Zhang; Liwei Zhang; Wei Hou; Yaning Wei (Functional & Integrative Genomics, 2022)

Validity Analysis of the Morphological Identification of Three Highly Morphologically Similar Species Belonging to the Genus Niviventer (Rodentia: Muridae) - Yao-Yao Li; Hao-Tian Li; Jia-Wei Hao; Chen-Yi Zhang; Guan-Ze Liu; Xing-Han Lin; Xiao-Qing Sun; Guo-Chen Zang; Yu-Chun Li (Journal of Mammalian Evolution, 2022)

Responses of nitrous oxide fluxes to autumn freeze–thaw cycles in permafrost peatlands of the Da Xing’an Mountains, Northeast China - Liquan Song; Shuying Zang; Lin Lin; Boquan Lu; Chaofeng Sun; Yaqing Jiao; Hanxi Wang (Environmental Science and Pollution Research, 2022)

Simultaneous detection of ten kinds of insecticide residues in honey and pollen using UPLC-MS/MS with graphene and carbon nanotubes as adsorption and purification materials - Xiuyu Pang; Chenyu Li; Chuanjiang Zang; Lei Guan; Peng Zhang; Chunxiang Di; Nan Zou; Beixing Li; Wei Mu; Jin Lin (Environmental Science and Pollution Research, 2022)

Estimation of permafrost thermal behavior using Fourier series model - Yan-yu Zhang; Shu-ying Zang; Lin Zhao; Da-long Ma; Yue Lin; Hao Li (Journal of Mountain Science, 2022)

The ATP Level in the mPFC Mediates the Antidepressant Effect of Calorie Restriction - Qian Wang; Ying Kong; Song Lin; Ding-Yu Wu; Jian Hu; Lang Huang; Wen-Si Zang; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

Comparison of pramipexole and levodopa/benserazide combination therapy versus levodopa/benserazide monotherapy in the treatment of Parkinson’s disease: a systematic review and meta-analysis - De-Qi Jiang; Qing-Min Zang; Li-Lin Jiang; Yan Wang; Ming-Xing Li; Jing-Yi Qiao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Estimation and Long-term Trend Analysis of Surface Solar Radiation in Antarctica: A Case Study of Zhongshan Station - Zhaoliang Zeng; Zemin Wang; Minghu Ding; Xiangdong Zheng; Xiaoyu Sun; Wei Zhu; Kongju Zhu; Jiachun An; Lin Zang; Jianping Guo; Baojun Zhang (Advances in Atmospheric Sciences, 2021)

Biosynthesis and preparation of phycoerythrobilin in recombinant Escherichia coli - Wenjun Li; Chengbo Ma; Baosheng Ge; Fan Zang; Song Qin; Jian Lin (Journal of Applied Phycology, 2021)

H2S probe CPC inhibits autophagy and promotes apoptosis by inhibiting glutathionylation of Keap1 at Cys434 - Na Li; JuYuan Wang; XiaoLing Zang; ZhaoYang Wang; Tao Zhang; BaoXiang Zhao; JunYing Miao; ZhaoMin Lin (Apoptosis, 2021)

Preparation of high-purity R-phycoerythrin and R-phycocyanin from Pyropia yezoensis in membrane chromatography - Fan Zang; Song Qin; Chengbo Ma; Wenjun Li; Jian Lin (Journal of Applied Phycology, 2020)

Molecular cloning of the cpeT gene encoding a bilin lyase responsible for attachment of phycoerythrobilin to Cys-158 on the β-subunit of phycoerythrin in Gracilariopsis lemaneiformis - Xuexue Cao; Xiaonan Zang; Zhu Liu; Yuming Jin; Deguang Sun; Yalin Guo; Zhendong Wang; Feng Zhang; Jiaojiao Lin (Journal of Applied Phycology, 2019)

Association analysis between feed efficiency and expression of key genes of the avTOR signaling pathway in meat-type ducks - Lei Yang; Tingting He; Yuan Xu; He Zang; Jiafa Wang; Zhiqiang Lin; Sihua Jin; Zhaoyu Geng (Molecular Biology Reports, 2019)

Cloning of ho gene from Gracilariopsis lemaneiformis and study on its function on the synthesis of a fluorescent phycoerythrobilin in heterologous hosts - Yuming Jin; Xiaonan Zang; Xiaoyun Huang; Xuexue Cao; Deguang Sun; Jiaojiao Lin; Zhu Liu; Chang Liu; Yalin Guo; Zhendong Wang; Lulu Hou (Journal of Applied Phycology, 2018)

Trichogramma parasitoids can distinguish between fertilized and unfertilized host eggs - Wen-Mei Du; Jing Xu; Yang-Yang Hou; Ying Lin; Lian-Sheng Zang; Xiangbing Yang; Jun-Jie Zhang; Chang-Chun Ruan; Nicolas Desneux (Journal of Pest Science, 2018)

PreSurgMapp: a MATLAB Toolbox for Presurgical Mapping of Eloquent Functional Areas Based on Task-Related and Resting-State Functional MRI - Huiyuan Huang; Zhongxiang Ding; Dewang Mao; Jianhua Yuan; Fangmei Zhu; Shuda Chen; Yan Xu; Lin Lou; Xiaoyan Feng; Le Qi; Wusi Qiu; Han Zhang; et al. (Neuroinformatics, 2016)

Functional analysis of PI-like gene in relation to flower development from bamboo (Bambusa oldhamii) - LONGFEI ZHU; YAN SHI; QIAOLU ZANG; QUAN SHI; SHINAN LIU; YINGWU XU; XINCHUN LIN (Journal of Genetics, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Within-litter variation in birth weight: impact of nutritional status in the sow - Tao-lin Yuan; Yu-hua Zhu; Meng Shi; Tian-tian Li; Na Li; Guo-yao Wu; Fuller W. Bazer; Jian-jun Zang; Feng-lai Wang; Jun-jun Wang (Journal of Zhejiang University-SCIENCE B, 2015)

A novel method to identify the DNA motifs recognized by a defined transcription factor - Xiaoyu Ji; Liuqiang Wang; Xianguang Nie; Lin He; Dandan Zang; Yujia Liu; Bing Zhang; Yucheng Wang (Plant Molecular Biology, 2014)

The ecological adaptability of four typical plants during the early successional stage of a tropical rainforest - P.L. Mao; R.Z. Zang; H.B. Shao; Y.D. Li; M.X. Lin; J.B. Yu (Plant Biosystems, 2014)

Renin–Angiotensin System Modulates Neurotransmitters in the Paraventricular Nucleus and Contributes to Angiotensin II-Induced Hypertensive Response - Jie Qi; Dong-Mei Zhang; Yu-Ping Suo; Xin-Ai Song; Xiao-Jing Yu; Carrie Elks; Yuan-Xi Lin; Yan-Yan Xu; Wei-Jin Zang; Zhiming Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2013)

Stable cell-surface expression of Japanese flounder growth hormone in yeast Saccharomyces cerevisiae and growth-promoting effect on juvenile fish by oral administration - Bin Liu; Xiao-Nan Zang; Xin-Fu Liu; Xue-Cheng Zhang; Ji-Lin Lei (Fisheries Science, 2012)

Comparison of Relationships Between pH, Dissolved Oxygen and Chlorophyll a for Aquaculture and Non-aquaculture Waters - Changjuan Zang; Suiliang Huang; Min Wu; Shenglan Du; Miklas Scholz; Feng Gao; Chao Lin; Yong Guo; Yu Dong (Water, Air, & Soil Pollution, 2011)

Synthesis and characterization of graft copolymer of chitosan and polyethylene glycol - Yan Zhao; Yiyi Sun; Zhihe Zang; Xiaohong Xu; Zhonglin Zhang; Ling Zhong; Wang Zan; Yan Zhao; Lin Sun (Molecular Biology Reports, 2011)

Experimental investigation of the immunoregulatory and anti-inflammatory effects of the traditional Chinese medicine “Li-Yan Zhi-Ke Granule” for relieving chronic pharyngitis in rats - Yiyi Sun; Zhihe Zang; Xiaohong Xu; Zhonglin Zhang; Ling Zhong; Wang Zan; Yan Zhao; Lin Sun (Molecular Biology Reports, 2011)